2011
DOI: 10.1177/1403494810391526
|View full text |Cite
|
Sign up to set email alerts
|

Vacations to sunny destinations, sunburn, and intention to tan: A cross-sectional study in Denmark, 2007-2009

Abstract: Taking a vacation in a sunny place is a risk factor for sunburn, especially for young people. The recommendation for sunscreen use should be re-evaluated, as intention to tan is the most important factor in sunburn on vacation and should be targeted more strategically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Additional important risk factors include sunbathing during times associated with the greatest UV risk (11 AM -3 PM), complete or inadequate sunscreen use during adulthood, as well as regular holidays in the mountains during the winter, spring and summer. These results agree with the observations of Koster et al and Moehrle [30,31].…”
Section: Discussionsupporting
confidence: 94%
“…Additional important risk factors include sunbathing during times associated with the greatest UV risk (11 AM -3 PM), complete or inadequate sunscreen use during adulthood, as well as regular holidays in the mountains during the winter, spring and summer. These results agree with the observations of Koster et al and Moehrle [30,31].…”
Section: Discussionsupporting
confidence: 94%
“…The campaign also promoted early detection of changes in moles. A video clip on sunbed use on YouTube achieved viral dissemination, with 14 million viewings, and was followed by a decrease in the use of indoor tanning beds [40]. Sun prevention campaigns (awareness) and melanoma screening programmes are associated with increased melanoma incidence rates through the detection of prevalent, slow-growing tumours [2,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The main established risk factors are a history of intermittent sun exposure, sunburn, age, immunosuppression, and phenotypic factors such as genetic susceptibility, gender, family history of melanoma, fair complexion and a large number of naevi [4,37]. While exposure to UV radiation is a well-known risk factor for skin cancer in Denmark [38], many Danes go on holidays in sunny locations with the expressed aim of sunbathing [39], and sun holidays have been found to contribute to the frequency of sunburn experienced by Danes [40]. This has been further substantiated by a recent observational study investigating the relationship between UV exposure and sunburn in 25 Danish sun-seekers during a week's holiday in the Canary Islands [39]; the percentage of the body surface area with sunburn was determined by daily skin examination, and the authors found that 100% of the Danes got sunburned during the holiday.…”
Section: Discussionmentioning
confidence: 99%
“…Because interest reaches a bottom during winter time, it would be of interest that public health initiatives organize a second campaign of information during this period. Scandinavians and Finns tend to take sunny vacations to South Europe or the Far East during winter, increasing the risk of excessive sun exposure and sunburns [8, 9]. …”
Section: Discussionmentioning
confidence: 99%